PELAKSAAN PENETAPAN NILAI LIMIT PADA OBJEK LELANG HAK TANGGUNGAN OLEH PT. BANK MANDIRI, TBK BUSINESS BANKING CENTER PEKANBARU - Sinaga, Butet Tiara; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Auction activities are sales that offer prices that are getting lower or lower.Auction is considered as the main way to resolve problem loans. The definition ofthe auction is contained in Article 1 of Decree of the Minister of Finance Number27 / PMK.06 / 2016 Regarding the Bidding Implementation Guideline whichstates that: reach the highest price, which is preceded by an auctionannouncement. "In the case of Bank Mandiri vs. Meini Supriatni, Meini Supriatni as thedebtor has defaulted so that her credit guarantees are auctioned by an independentbank with the broker KPKNL Pekanbaru. The value of the limit offered by anindependent bank is considered very low and the offer of credit collateral goodsonly attract 1 (one) buyer, so the proceeds from the sale of the credit guarantee arethe same as the value of the offered limit plus the auction fee. This is certainlydetrimental to the debtor as the previous owner of the collateral.In this study the authors use the empirical method, another term used issociological. This descriptive sociological research was carried out in the area ofBank Mandiri, Tbk, Pekanbaru Business Banking and the Office of State Assetsand Auction Services in Pekanbaru.From the research and discussion, it concludes that, firstly theimplementation of the determination of the limit value on the auction object is theauthority of the seller, the low limit value is the responsibility of the seller. In thelaw, it has not been explained in more detail how the method of determining thelimit value is implemented. Second, the seller's responsibility for setting limitvalues has not been regulated in detail in the law, resulting in a legal vacuum thatcreates a legal dispute. If according to the debtor the value of the limit set at theauction object is too low, the debtor will sue the creditor in relation to the resultsof the auction whose limit value is low.Keywords: Low-Limit Value-Assurance Auction